Fábricas e tendas de ferro em dinâmicas escravistas, termo de Santa Bárbara, Minas Gerais, 1822 1888 - Martha Rebelatto (2012)
This thesis deals with the economic activities involving slave labor, alone or in conjunction with other forms of labor, in the period of 1822-1888 within the boundaries of Santa Barbara, Minas Gerais, Brazil. The research was based on the analysis of several sources: nominative lists, population maps, the 1872 census, inventories, tax lists andcorrespondence between the President of the Province and local authorities. Identifying constraints and opportunities that the spatial geography in connection with the technologies of the time had on regional activities helps to understand the variations in the use of captivelabor, core and complementary activities, commercial and economic transformations. The surroundings of Santa Barbara proved to be an area of interest for the study since during the nineteenth century, it aggregated a wide variety of economic activity from the regionally traditional, such as gold mining and agriculture, to manufacturing activities (such asironworks and weaving, for instance), which gained greater prominence in the period. This diversity enabled the identification of adaptations that have shaped the regional economy. In other words, the strategies used by individuals living there to manage their assets and capital, be they small or large fortunes. The analysis of a long period of time in a relatively restricted space allows us to explain the economy and employment of slave labor, marking changes, adaptations and continuities in the local economic and "labor" practices.